PENGARUH BIOPESTISIDA NABATI DAN MEDIA TANAM TERHADAP PRODUKSI TANAMAN TOMAT (Lycopersium esculentum L.) - Niga, Regina Magi; Indawan, Edyson; Fikrinda, Wahyu (Universitas Tribhuwana Tunggadewi, 2017)
The study has the objective to determine the effectiveness of plant-based biopesticides and growing media in increased production of tomato plants. Research using (RAK) factorial of two factors, namely vegetable and Bokashi biopesticides. Each consists of 4 levels of treatment trials (Factor) A: A0 = Control (without biopesticides vegetable), A1 = 20 ml / l, A2 = 40 ml / l, A3 = 60 ml / l, while the second factor consisted of 4 level of treatment (factor) B: B0 = Control (without bokashi), B1 = 5.5 kg Soil and bokashi 5 ton / ha (0,5kg / polybag), B2 = Land bokashi 5 kg and 10 tonnes / ha (1 kg / polybag), B3 = Land 4.5 kg and bokashi 15 ton (1.5 kg / polybag), in order to get 16 combinations, repeated 4 times obtained 64 experimental unit. Each experimental unit there are two plants so that the total of plants used in the trial was 128 plants. Results showed treatment with a dose Bokashi (B3: 15 ton / ha (1.5 kg / polybag) real effect on tomato plant height parameter HST at age 35, the number of leaf age 35 HST numbered, leaf area age 23 HST, and the amount of interest age 33 HST 11.03 a flower, because of nutrient content contained in bokashi able to add height to the stems of tomato plants. Giving bokashi doses (B1: 0.5 kg / polybag) real effect on the number of majority age of 78 HST fruit and fruit weight weighing the age of 78 DAP. biopesticides vegetable given no real effect, except parameter number of leaf age 35 HST. bokashi effective treatment for each parameter observation while biopesticides vegetable tomato plants on the observation of the number of leaves of tomato plants of age 35 HST, the other is not effective. Penelitian memiliki tujuan untuk menentukan keefektifan biopestisida nabati dan media tanam dalam peningkatan produksi tanaman tomat. Penelitian menggunakan (RAK) faktorial dua faktor yaitu biopestisida nabati dan bokashi. Masing-masing terdiri dari 4 taraf perlakuan percobaan, sehingga didapat 16 kombinasi, diulang sebanyak 4 kali diperoleh 64 satuan percobaan. Setiap satuan percobaan terdapat 2 tanaman sehingga total tanaman yang digunakan pada percobaan adalah 128 tanaman. Hasil penelitian menunjukkan Perlakuan bokashi dengan dosis (B3 : 1,5 kg/polybag) berpengaruh nyata pada parameter tinggi tanaman tomat umur 35 HST sebesar, jumlah daun umur 35 HST berjumlah, luas daun umur 23 HST, dan jumlah bunga umur 33 HST sejumlah 11,03 bunga, karena kandungan hara yang terdapat dalam bokashi mampu menambah tinggi pada batang tanaman tomat. Pemberian bokashi dengan dosis (B1 : 0,5 kg/polybag) berpengaruh nyata pada jumlah buah terbanyak umur 78 HST dan bobot buah seberat umur 78 HST. Biopestisida nabati yang diberikan tidak berpengaruh nyata, kecuali parameter jumlah daun umur 35 HST. Perlakuan bokashi efektif pada setiap parameter pengamatan tanaman tomat sedangkan biopestisida nabati pada pengamatan jumlah daun tanaman tomat umur 35 HST, yang lainnya tidak efektif.